Agentes comunitários de saúde no Brasil e educação popular: das práticas voluntárias nas organizações de base aos serviços permanentes nas instituições públicas - Bandeira, Francikely da Cunha (2022)
The current Health Community Agents represent a synthesis of various community health experiences coming out and strengthened in the country, especially in the 1970s and 1980s, most of them developed from community initiatives from/in which appeared the first Health Agents. In a dictatorial context, after 1964, part of the Church carried out an important role in the regimentation and Policy Training of the Agents from/in base communities through the Base Ecclesial Communities – BEC. In Ceará, experiences were observed with the so-called Health Agents since the 1970s and, consequently, in 1989, the drought confrontation led to the establishment of the Health Agents Programme– HAP, in the State. In parallel, community health experiences were carried out in various places around the country, as in Recife and São Paulo – SP. In 1991, the Health Ministry, with resistance in the health professionals’ field, recognized the potential of the existing experiences, captured the relevance of those experiences and the different types of agents, and institutionalized the National Community Health Agent Programme – NCAP. Facing this scenario, the aim of the research is to understand the processes of the institutionalization of the Community Health Agent Programme, that stem from a historical journey, since the base volunteer organizations to the space for permanent services in public institutions identifying the first changes occurred in the process. We identified community health experiences (here are understood as instituting movements) in addition to (re)build Ceará experiences, in order to verify how have the processes forged the agents and as they unfolded (understood as institutionalization moment) till the moment of the “creation” and consolidation of the National Community Health Agent Programme at a national level (understood as the instituted moment) observing some progress and failures of the Community Health Agents historic evolution. We are based on the concepts of grassroots organizations, solidarity, institutionalization and bureaucracy. We used as methodological resource the hermeneutics in a philosophical way, with a view to the main focus of the study, to achieve understandings issuing guidelines that experienced the category paths sense. The great challenge was to understand the experiences paths until its arrival to the public spaces identifying gains or losses in the light of Popular Education seen here as social transformation tool. The research showed that the CHA have great potential for collective action and that it must be strengthened from the popular role point of view as well as recognized from the institutional point of view.